2008
DOI: 10.1007/s00122-008-0861-9
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in cytosine methylation and species-specific transcription induced by interspecific hybridization between Oryza sativa and O. officinalis

Abstract: Interspecific hybridization and polyploidization may involve programmed genetic and epigenetic changes. In this study, we used the methylation-sensitive amplified polymorphism (MSAP) method to survey cytosine methylation alterations that occurred in F(1) hybrid and BC(1) progeny following interspecific hybridization between Oryza sativa and O. officinalis. Across all 316 parental methylated sites, 25 (7.9%) cytosine methylation alterations were detected in the F(1) and/or BC(1) progeny. Thirty additional cytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…However, crosses between genetically similar parents such as Arabidopsis accessions or subspecies of rice can produce hybrids displaying significant heterosis, apparently breaking down the relationship between genetic distance and extent of hybrid vigor (6, 7). It has been reported that the epigenome evolves at a significantly faster rate than the genetic sequence (8-10), consistent with genetically similar parents having markedly different epigenomes (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). These epigenomic systems, such as DNA methylation and small RNAs, play a vital role in genomic stability, development, and the regulation of genes within a plant.…”
mentioning
confidence: 85%
“…However, crosses between genetically similar parents such as Arabidopsis accessions or subspecies of rice can produce hybrids displaying significant heterosis, apparently breaking down the relationship between genetic distance and extent of hybrid vigor (6, 7). It has been reported that the epigenome evolves at a significantly faster rate than the genetic sequence (8-10), consistent with genetically similar parents having markedly different epigenomes (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). These epigenomic systems, such as DNA methylation and small RNAs, play a vital role in genomic stability, development, and the regulation of genes within a plant.…”
mentioning
confidence: 85%
“…Further sequencing results of the methylation polymorphism fragments confirmed that most of the DNA methylation alteration happened at the repetitive sequences or non-coding sequences. However, the movement of transposable elements induced by DNA methylation alteration played an important role in the regulation of gene expression (Jin et al, 2008;Xu et al, 2009). The potential impacts, especially methylation alternation of transposable elements should be investigated on PD0111 and PD0113.…”
Section: Discussionmentioning
confidence: 99%
“…The important role of cytosine methylation in epigenetic regulation of gene expression has been well documented (Jin et al, 2008). DNA methylation is closely related to gene expression, and it appears that different methylated regions in genes have different effects on gene expression (Lou et al, 2014).…”
Section: Relationship Between Gene Body Methylation and Expression Ofmentioning
confidence: 99%